2023
DOI: 10.1109/tmi.2022.3221890
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-Reg: Interpretable Classification and Regression With Feature Attribution for Mapping Neurological Phenotypes in Individual Scans

Abstract: An important goal of medical imaging is to be able to precisely detect patterns of disease specific to individual scans; however, this is challenged in brain imaging by the degree of heterogeneity of shape and appearance. Traditional methods, based on image registration, historically fail to detect variable features of disease, as they utilise population-based analyses, suited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Since Varela et al showed that LA anatomy is a significant factor in prediction of AF recurrence post ablation ( Varela et al, 2017a ), the DL approach of the study should be extended to 3D LA images and simulations. Future work should also focus on using exclusively real patient LA data and investigating intrinsically interpretable DL models such as ICAM ( Bass et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since Varela et al showed that LA anatomy is a significant factor in prediction of AF recurrence post ablation ( Varela et al, 2017a ), the DL approach of the study should be extended to 3D LA images and simulations. Future work should also focus on using exclusively real patient LA data and investigating intrinsically interpretable DL models such as ICAM ( Bass et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent time, approaches to simultaneous classification and feature attribution are being developed using a shared latent space of attributes with a classification layer: VA-GAN [ 148 ], ICAM [ 149 ]. These methods imply learning on the basis of generative networks being not always successful on a small data sample of medical tasks.…”
Section: Section 3 Utilizing Data Analysis and Machine Lear...mentioning
confidence: 99%
“…For example, Bass, Silva, Sudre, et al . [19], [20] used a VAE-GAN [21], with separate content and attribute encodings, to disentangle class specific features of disease, from class irrelevant features of cortical shape variation, to map patterns of disease related brain atrophy in individuals with mild cognitive impairment (MCI) or Alzheimer’s disease (AD). Others models have sought to improve interpretability by incorporating confounding factors, such as age: for example, Ravi, Alexander, Oxtoby, et al .…”
Section: Introductionmentioning
confidence: 99%